INTERFACE DESIGN TEMPERATURE CONTROL SYSTEM USING COMPUTER PROGRAMMING BASED LANGUAGES C - Ari ibowo Susanto; Fivtatianti Hendajani, Skom., MM Fivtatianti Hendajani, Skom., MM (Jurnal Sistem Informasi, 2005)
Along with the development of science and technology, has had a positive impact in the industrial world, especially in the utilization of the temperature measurement system that uses the principle of data acquisition. With the computer, then use the computer to control a temperature measurement system is now a practical and common. In industries that require extremely high temperatures on the production process, the temperature must be kept at certain temperatures. Therefore, this paper aims to facilitate the temperature control in an industry that requires high temperatures in its operations.At this writing, the series of temperature control systems can work well, although there are deviations from the value of the actual value. This is supported by the performance of each component in the system. If each component in the system can work in accordance with their respective functions, the system will have the reliability (reliability) in order to work properly.For ease in the observation, the authors use a table test. Table test was used to ascertain level deviations from the data obtained with actual data. Table testing can also be used as a way to process the data using least squares method, so it is easy in analyzing.At this writing, the authors analyze this control system with the way this system divides into several blocks of the circuit. From each of these circuit blocks will be determined the value of its output, so it can ascertain performance in each block. Obtaining the value of output is shown in the table experiments and processed using the least square method to determine the level of its deviation. Of this paper can then be developed into a more useful applications, such as incubators. Writing is very useful especially for students who want to deepen their computer system about temperature control system. And generally to the reader, either the hobbyist or a company or industry that uses a system of temperature control in process operations.